Training adult laypeople in basic life support to enhance knowledge and confidence - Priyo Sasmito; Nur Fajariyah; Dina Rasmita; Mugi Hartoyo; Nisa Arifani; Yeni Koto (Malahayati International Journal of Nursing and Health Science, 2023)
Background: The lack ability of community to provide first aid to victims who experience cardiac arrest is due to their lack of knowledge and skills. Adolescent to adult age group has good potential to be involved in efforts to provide resuscitation for Out-of-Hospital cardiac arrest (OHCA) cases.Purpose: To determine the effect of training adult laypeople in basic life support to enhance knowledge and confidenceMethod: A quasi-experimental study with 1 pre and post-test group with a total sample of 30 members of youth organizations taken with total sampling technique.Results: There was an increase in respondents' knowledge by an average of 58.89 from the initial knowledge with an average score of 30 (poor) to 88.89 (good). The results of statistical calculations using the Wilcoxon Signed Rank Test with a level of significance (α) 0.05 showed that calculated W value smaller than W table and the p value 0.000 smaller than α 0.05.  There was also an increase in respondents' self-confidence of performing BLS from an average of 43.67 (less confident) to an average of 88.00 (very confident) after BLS training. Calculated W value is smaller than W table and p value 0,000 smaller than α 0.05.Conclusion: BLS training has a significant effect on the knowledge and self-confidence level of respondents. There is an increase in the level of knowledge and confidence of respondents in the age group of adolescents and young adults to perform resuscitation after receiving BLS training.